Seafarers’ Job Stress and Subjective Well-Being: The Mediating Effect of Psychological Resilience and the Moderating Effect of Organizational Support - Kaya Ozbag, Gonul (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Subjective well-being (SWB) has been widely reported to have a pivotal impact on the individual, yet its application in the marine professions remains unexplored. Thus, in the current work, proposing seafarers’ psychological resilience (PR) as a mediator and organizational support (OS) as a moderator, the connection between job stress (JS) and SWB was explored. A survey of seafarers from sailing on merchant ships operating internationally were analyzed with partial least squares structural equation modelling methods. The findings indicate a complete mediation effect of PR on the relationship between JS and SWB. However, the results do not provide any empirical evidence regarding the contingency of OS on the relationship between PR and SWB. This study contributes to the existing literature as it examines the role of individual, organizational, and job elements in a more detailed model of SWB. Knowledge about such elements would highlight challenging areas within seafaring and thereby enable to work out prevention and intervention strategies to improve and develop well-being at sea.